Identification of the whole genome of alternative splicing and RNA-binding proteins involved in nintedanib-induced apoptosis in gastric cancer cells - Dong, Xiaohua; Liu, Zhilong; Yu, Miao; Yang, Xiaojun; Cai, Hui (PeerJ, 2024)
Background It has been demonstrated that nintedanib can inhibit the proliferation of gastric cancer cells, but the specific mechanism of action is unclear. Objective Investigating the changes of key factors involved in gene transcription and post-transcriptional regulation during the process of treating gastric cancer with nintedanib. Methods In this study, we performed transcriptome sequencing on gastric cancer cell groups treated with nintedanib and control groups. The SUVA (Splice sites Usage Variation Analysis) software was used to identify differential alternative splicing (AS) events between the nintedanib-treated group and the control group. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were conducted to assess the functional differences and pathways associated with these events. Finally, a co-expression regulatory network of differentially expressed RNA-binding proteins (RBPs) and differentially spliced genes was established. Results: A total of 915 differential AS events were identified between the two groups, and these differential genes were closely related to the apoptosis pathway. Further analysis revealed that differential RBPs (TAGLN2, TAGLN, SRSF6, PKM, SRSF2, NOC2L, IPO4, C1QBP, DHX9) may affect the anti-proliferative effect of nintedanib on gastric cancer cells by regulating downstream genes involved in cell proliferation and angiogenesis (NR4A1, BBC3, IFI27) through alternative splicing. Conclusion This study systematically identified important changes in alternative splicing and RNA-binding proteins during the process of nintedanib-induced apoptosis in gastric cancer cells. It innovatively revealed the mechanisms of action of nintedanib in gastric cancer cells and expanded the selection of new targets for gastric cancer treatment.
Keywords: Gastric cancer; RNA-sequencing; Alternative splicing; RNA-binding proteins